Sistem Informasi Penggajian Karyawan pada UMKM “Makaroni Ira” - adminjftr adminjftr; Zakiya Muallifa Rahman (Fakultas Teknik dan Rekayasa, 2022)
An information system is a system that, apart from performing all the transaction processing is necessary for an organization, also provides information and processing support for management and decision-making functions. Every organization always needs systems to collect, process, store, review and distribute information.